Beloved in Mahwee’s Poems - Pary Omar Ali; Srwa Tahhir Ali Mohammed; Bestoon Abubakr Ali; Hemn Karim M. Salih (QALAAI ZANIST JOURNAL, 2023)
Love and woman are the main topics, which became poets’ sources of inspiration and invention; whether it is intrinsic love (Divine Love) or extrinsic love (Female Love). This research that entitled “Beloved in Mahwee’s Poems” is an attempt to introduce Beloved by the poet. The research consists of two main sections, conclusion and list of sources: the first section is deals with the method of semantic scientifically and the diversity of meaning, meanwhile it illustrates that because of over-used of certain words by communities, authors and poets, they pregnant with varying meanings and connotation. Also, this section indicates varying meaning in linguistics in a scientific way. Then generally it covers the beloved by Kurdish Classic poets, with providing adequate samples of poems by so-called poets. The second section, is in details and generally explains the meaning of beloved in Mahwee’s poems, which carries varying meanings, such as: Almighty God, The Messenger of God (PUH), etc... Finally, it poses conclusion and list of sources of the research